Macroeconomic Shocks and Trade Flows within Sub-Saharan Africa : Implications for Optimum Currency Arrangements - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 1995)
Africa has more countries than any other continent, and hence the largest number of potential monetary and exchange rate arrangements. This paper looks at whether the existing highly fractured monetary arrangements in Sub-Saharan Africa correspond to what might be expected from the theory of optimum currency areas. This is done by analyzing both the size and correlation of real disturbances across countries and the level of intra-regional trade. The results indicate little evidence that Sub-Saharan African countries would benefit in the near future from larger currency unions.